2020
DOI: 10.1038/s41398-020-00988-y
|View full text |Cite|
|
Sign up to set email alerts
|

Mesenchymal stem cells derived extracellular vesicles improve behavioral and biochemical deficits in a phencyclidine model of schizophrenia

Abstract: Schizophrenia is a debilitating psychiatric disorder with a significant number of patients not adequately responding to treatment. Phencyclidine (PCP) is used as a validated model for schizophrenia, shown to reliably induce positive, negative and cognitive-like behaviors in rodents. It was previously shown in our lab that behavioral phenotypes of PCP-treated mice can be alleviated after intracranial transplantation of mesenchymal stem cells (MSC). Here, we assessed the feasibility of intranasal delivery of MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 80 publications
(99 reference statements)
0
31
0
Order By: Relevance
“…In addition, there was also an improvement in schizophrenic behaviors such as social interactions and disruption in prepulse inhibition. EVs were able to migrate and localize in the prefrontal cortex of treated mice, which is a crucial region involved in the pathogenicity of schizophrenia 49 . These results indicate that treatment with EVs can prevent or ameliorate symptoms of neurodevelopmental disorders in animal models, with the therapeutic potential to activate molecular and protein changes in the neurons.…”
Section: Therapeutic Effect Of Evs In Neurological Disordersmentioning
confidence: 73%
See 2 more Smart Citations
“…In addition, there was also an improvement in schizophrenic behaviors such as social interactions and disruption in prepulse inhibition. EVs were able to migrate and localize in the prefrontal cortex of treated mice, which is a crucial region involved in the pathogenicity of schizophrenia 49 . These results indicate that treatment with EVs can prevent or ameliorate symptoms of neurodevelopmental disorders in animal models, with the therapeutic potential to activate molecular and protein changes in the neurons.…”
Section: Therapeutic Effect Of Evs In Neurological Disordersmentioning
confidence: 73%
“…IN administration of EVs provides an effective strategy to treat a variety of CNS pathologies, including neurodegenerative diseases such as Parkinson's disease (PD), 44 MS, 34 and Alzheimer's disease (AD), 45‐47 psychiatric disorders including autism 32,48 and schizophrenia, 49 and neurotrauma such as that caused by perinatal brain injury, 50 status epilepticus (SE), 42,51 and traumatic brain damage (TBI) 52 …”
Section: Treatment Of Cns Disorders By Nasal Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Beneficial effects of intranasally injected MSC-Exos in the improvement of cognitive function were observed in phencyclidine (PCP)-treated mice, a well-established murine model of schizophrenia [ 51 ]. Tsivion-Visbord and colleagues demonstrated that intranasal delivery of MSC-Exos managed to alleviate schizophrenia-like behaviors by preserving viability of Gamma aminobutyric acid (GABA)-producing neurons and by modulating activity of neurotransmitters in the CNS [ 51 ]. Immediately after injection, the majority of MSC-Exos accumulated in the neurons of the prefrontal cortex (PFC), the brain area that is the most severely affected in schizophrenia.…”
Section: Therapeutic Effects Of Msc-exos In the Treatment Of Parkimentioning
confidence: 99%
“…Significantly reduced glutamate levels in the cerebrospinal fluid and a remarkably increased number of GABA-producing neurons were observed in PFC of PCP-treated mice that received MSC-Exos. Importantly, MSC-Exos improved social interaction and disruption in prepulse inhibition in PCP-treated mice, significantly attenuating schizophrenia-like behavior [ 51 ]. Since no negative symptoms were detected following intranasal administration of MSC-Exos in mice [ 50 , 51 ], efficacy of this non-invasive therapeutic approach should be further explored in upcoming clinical studies for the amelioration of behavioral symptoms in patients suffering from schizophrenia and ASD.…”
Section: Therapeutic Effects Of Msc-exos In the Treatment Of Parkimentioning
confidence: 99%